Quality characteristics of the enhanced beef using winter mushroom juice - Choi, Yun-Sang (J Anim Sci Technol, 2020)
This study investigated the quality properties of enhanced beef, manufactured by injecting the beef with a brine containing winter mushroom juice powder (WMJP). The enhanced beef was manufactured by injecting the eye of round with brine (15% by green weight). Four treatments consisted of control (no injection of brine) and three enhanced beef, EBS (brine containing 5 g sodium chloride per kg beef), EBW 0.2 (brine containing 5 g sodium chloride and 2 g WMJP per kg beef), and EBW 0.5 (brine containing 5 g sodium chloride and 5 g WMJP per kg beef), were tested. The effect of enhancement or WMJP on the quality properties of beef was evaluated during storage at 4°C for 1, 5, and 10 days. Total aerobic bacteria counts between the control and the enhanced beef, and among EBS, EBW 0.2, and EBW 0.5 were not significantly different after any storage period (p > 0.05). The pH of beef was not different between the control and the enhanced beef, and among enhanced beef at 1 and 5 days of storage (p > 0.05). However, it was higher in the enhanced beef than control, and EBW 0.2 and EBW 0.5 had higher pH than EBS after 10 days of storage (p < 0.05). The enhanced beef showed a high total loss at all storage days (p < 0.05). There were no differences in total loss among enhanced beef after any storage period (p > 0.05). The enhanced beef had no consistent differences in L*, a*, and b* values with control during storage, however, EBW 0.5 showed high color stability. The hardness of the enhanced beef was significantly lower than that of the control after 10 days of storage, although the values were lower at all storage stages. EBS 0.5 had the lowest thiobarbituric acid reactive substance (TBARS) value among cooked beef of all treatments at all storage days. The enhanced beef received higher scores in all sensory properties than control, and no negative effect of WMJP was found in the sensory quality of the enhanced beef. The use of winter mushroom juice can result in quality improvement in enhanced beef.